Privacy issues in libraries with online services: attitudes and concerns of academic librarians and university students in Ghana - Avuglah, Bright, Kwaku; Owusu-Ansah, Christopher; Tachie-Donkor, Gloria; Yeboah, Eugene Baah (My University, 2020)
The study surveyed librarians’ and students’ attitudes, perceptions and concerns on privacy in Ghanaian universities with the aim of seeking a better alignment of their perspectives in the online library context. This study adapted and applied the instrument developed by Zimmer which assessed attitudes and practices of librarians in the USA on privacy rights and protecting patron’s privacy in the library. The study found that between librarians and students in Ghanaian universities, there was a need for greater control over their personal data; and a need for ethical responsibility on the part of data collecting online library agents; both groups expressed dislike for state censorship and corporate monopoly over their personal data. However, despite their positive attitude about the strong role of librarians in guaranteeing their personal data, a significant number of them demonstrate little faith in librarians to actualize the protection of their personal data. Lastly, privacy attitudes and concerns of academic librarians were noted to align with that of university students in Ghana. Among others, it was recommended that Ghanaian academic librarians integrate privacy education and awareness creation in their universities, emphasizing the need to make informed online decisions and exposing potential repercussions of their decisions while using online library and digital resources.
Keywords: Academic library; Ghanaian Universities; Online library services; Patron privacy; Privacy attitude; Privacy concern; Privacy Literacy; Privacy paradox; Privacy protection; University of Cape Coast; University of Education Winneba; University of Ghana